Protocol for the process evaluation of a complex intervention delivered in schools to prevent adolescent depression: the Future Proofing Study. Issue 1 (12th January 2021) - Beames, Joanne R; Lingam, Raghu; Boydell, Katherine; Calear, Alison L; Torok, Michelle; Maston, Kate; Zbukvic, Isabel; Huckvale, Kit; Batterham, Philip J; Christensen, Helen; Werner-Seidler, Aliza
Abstract : Introduction: Process evaluations provide insight into how interventions are delivered across varying contexts and why interventions work in some contexts and not in others. This manuscript outlines the protocol for a process evaluation embedded in a cluster randomised trial of a digital depression prevention intervention delivered to secondary school students (the Future Proofing Study). The purpose is to describe the methods that will be used to capture process evaluation data within this trial. Methods and analysis: Using a hybrid type 1 design, a mixed-methods approach will be used with data collected in the intervention arm of the Future Proofing Study. Data collection methods will include semistructured interviews with school staff and study facilitators, automatically collected intervention usage data and participant questionnaires (completed by school staff, school counsellors, study facilitators and students). Information will be collected about: (1) how the intervention was implemented in schools, including fidelity; (2) school contextual factors and their association with intervention reach, uptake and acceptability; (3) how school staff, study facilitators and students responded to delivering or completing the intervention. How these factors relate to trial effectiveness outcomes will also be assessed. Overall synthesis of the data will provide school cluster-level and individual-level process outcomes. Ethics and dissemination: Ethics approval was obtained from the University of New South Wales (NSW) Human Research Ethics Committee (HC180836; 21st January 2019) and the NSW Government State Education Research Applications Process (SERAP 2019201; 19th August 2019). Results will be submitted for publication in peer-reviewed journals and discussed at conferences. Our process evaluation will contextualise the trial findings with respect to how the intervention may have worked in some schools but not in others. This evaluation will inform the development of a model for rolling out digital interventions for the prevention of mental illness in schools. Trial registration number: ANZCTRN12619000855123; https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=377664&isReview=true .